Pengaruh Konseling KB dengan Metode Pendekatan Keluarga terhadap Kesertaan Menjadi Akseptor KB di Wilayah Kerja Puskesmas Tepeleo Tahun 2025 - Rianti Rianti; Rifzul Maulina (STIKES Columbia Asia Medan, 2025)
One effort to address the increasing population in Indonesia is through the Family Planning (FP) program. One of the roles of midwives in implementing this program is through family planning counseling. This study aimed to determine the relationship between family planning counseling and participation as family planning acceptors in the Tepeleo Community Health Center (Puskesmas) work area. This study was conducted from October to November 2021. The analytical method used in this study was descriptive analytic, which examines the relationship between two variables in a situation or group of objects. The results were obtained by distributing questionnaires to 45 respondents and then tested using the Chi-Square test with a significance level of 0.05. The analysis results showed a relationship between family planning counseling and participation as family planning acceptors in the Tepeleo Community Health Center work area. Furthermore, the family planning counseling program was implemented quite well (84.4%), as indicated by community participation as family planning acceptors (88.9%).